The relation between maternal participation in pregnancy classes and EIBF accomplishment in Indonesia: An evident from nationally representative survey - Hastin Dyah Kusumawardani; Agung Dwi Laksono; Leny Latifah; Taufiq Hidayat; Setia Pranata; Yusi Dwi Nurcahyani (Clinical Epidemiology and Global Health)
Objectives: Prenatal Classes (PC) aim to increase the output of pregnancy and childbirth for mothers and their babies, including tutorials on the nutritional intake for children. The study analyzes the Prenatal Class's effectiveness on early initiation of breastfeeding (EIBF) in Indonesia. Methods: The cross-sectional study examined 2382 children under two years. Besides nutritional status (stature), the study analyzed ten independent variables (residence, maternal age, marital, maternal education, employment, wealth, children's age, gender, and early initiation breastfeeding (EIBF). We used a binary logistic regression test in the final stage. Results: The study informed that mothers with PC were 1.209 times more likely to achieve EIBF than those without (AOR 1.209; 95 % CI 1.205–1.213). Moreover, the results also found that all control variables were significantly related to EIBF achievement. Conclusion: The study concluded that PC effectively increases EIBF in Indonesia. Mothers with PC are more likely to achieve EIBF than those without. Furthermore, the study also found all control variables were significantly related to EIBF achievement.